A RESEARCH STUDY ON KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN STUDENTS` REALIZATION: A RESEARCH STUDY ON KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN STUDENTS` REALIZATION - Nikolova, Snezhana; Kirilov, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper presents the opinions of users, specialists and students who study at Konstantin Preslavsky University of Shumen. The period involved is 2009-2013. The paper analyzes the collected, processed and systematized data from two of the four questionnaires used by Shumen University – Questionnaire А3 for quality of education that is intended for employers and Questionnaire А4 that is intended for students who graduate Shumen University. http://uninet.shu-bg.net/upravlenienakachestvoto/anketi/.